2007
DOI: 10.1097/pec.0b013e31803f7552
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Airway Devices for Use in Children Requiring Prehospital Airway Management

Abstract: This manuscript reviews the latest literature on alternative airways for use in children requiring prehospital airway management. Case discussions serve as a springboard for discussion of alternatives to bag-mask ventilation and endotracheal intubation for management of ventilation in infants and children in the prehospital setting. Few airway procedures have been studied with any rigor in this setting, and most of the data that are available are extrapolated from adults. Laryngeal mask airway may be the best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 130 publications
0
8
0
2
Order By: Relevance
“…24 Also, there is increasing awareness of the possible role of supraglottic airway devices, such as the LMA TM , in children requiring pre-hospital airway management. 25 Furthermore, studies using simulation technology appear to show an advantage of the LMA TM over tracheal intubation during simulated pediatric cardiac arrest managed by paramedics. 26 In addition, a study of apneic anesthetized children showed that the LMA TM compared favourably with a facemask when used by critical care nurses as a means to ventilate the lungs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…24 Also, there is increasing awareness of the possible role of supraglottic airway devices, such as the LMA TM , in children requiring pre-hospital airway management. 25 Furthermore, studies using simulation technology appear to show an advantage of the LMA TM over tracheal intubation during simulated pediatric cardiac arrest managed by paramedics. 26 In addition, a study of apneic anesthetized children showed that the LMA TM compared favourably with a facemask when used by critical care nurses as a means to ventilate the lungs.…”
mentioning
confidence: 99%
“…24 En outre, on s'intéresse de plus en plus au rôle potentiel des dispositifs supraglottiques tels que le LMA TM chez les enfants nécessitant une prise en charge des voies aériennes avant leur arrivée à l'hôpital. 25 Qui plus est, des études utilisant des techniques de simulation semblent montrer un avantage du LMA TM par rapport à l'intubation trachéale pendant un arrêt cardiaque pédiatrique simulé pris en charge par des ambulanciers. 26 De plus, une étude portant sur des enfants anesthésiés et en apnée a montré que le LMA TM soutenait la comparaison avec un masque facial lorsqu'il était utilisé par des infirmières des soins intensifs afin de ventiler les poumons.…”
unclassified
“…3,5,6 In both simulation and field studies, the adult King LT-D has been more rapidly deployed with fewer attempts than both ETI and the Combitube. [7][8][9] The adult King LT-D airway has also been used successfully as part of a rapid-sequence intubation (RSI) protocol.…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, pediatric surgical cricothyrotomy in the field is generally not feasible because of difficulty identifying landmarks and the greater potential for serious complications. 3,4 Prehospital providers treating pediatric patients have been left without a safety net in the "can't intubate, can't ventilate" situations and without a means of securing an airway if intubation fails but ventilation is still possible.…”
Section: Introductionmentioning
confidence: 99%
“…A simple device such as a Guedel airway may be helpful in maintaining airway patency and, for those with the necessary experience, a laryngeal mask is often superior. However, neither device will be tolerated by the child with intact pharyngeal reflexes in whom their use may precipitate vomiting and aspiration [11]. Opening the airway and delivering supplementary oxygen may be all that is required in some circumstances such as airway obstruction due to sedative overdose.…”
Section: Early Intervention In Respiratory Failure and Shockmentioning
confidence: 99%